2013
DOI: 10.1089/cap.2012.0090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurofeedback Versus Stimulant Medication in Attention-Deficit/Hyperactivity Disorder: A Randomized Pilot Study

Abstract: Objective: The purpose of this pilot study was to compare the effects of 30 sessions of neurofeedback (NF) with stimulant medication on attention-deficit/hyperactivity disorder (ADHD) patients. Methods: Thirty-two medication-naïve ADHD patients, ages 7-16, from a neuropsychiatric clinic, were randomized to NF (n = 16) or drug treatment (n = 16). Other actions, such as parent management training, information, or support in school were given as needed, with no differences between the groups. All participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 49 publications
3
52
1
3
Order By: Relevance
“…Several randomized controlled trial studies have since compared neurofeedback to medication alone or in combination (see Table 2). Although one of them 54 found neurofeedback effects inferior to medication effects, the other 2 studies 55,56 found no differences between medication and neurofeedback effects, and one study 55 reported that neurofeedback or medication alone was as effective as the combination.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Several randomized controlled trial studies have since compared neurofeedback to medication alone or in combination (see Table 2). Although one of them 54 found neurofeedback effects inferior to medication effects, the other 2 studies 55,56 found no differences between medication and neurofeedback effects, and one study 55 reported that neurofeedback or medication alone was as effective as the combination.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…(Arnold et al, 2013), 13. (Ogrim & Hestad, 2013), 14. (Vollebregt, van Dongen-Boomsma, Buitelaar, & Slaats-Willemse, 2014, 15.…”
Section: Introductionunclassified
“…[8][9][10][11] Two of these experiments reported comparable improvements in attention between the neurofeedback and medication groups yet shied away from collecting neurological measures; 8,9 one showed similar changes in resting-state EEG activity yet neglected to ascertain whether attention actually improved; 10 the other suggested superiority of medication over EEG-neurofeedback in terms of both behaviour and neural activity. 11 Notably, these studies scantily report whether participants learned to modulate the brain signal of interest and thus provide little insight into the neural underpinnings of these effects. To promote EEGneurofeedback as a brain-regulation therapy, researchers will need to conduct high-quality clinical trials that confirm the alleged underlying neurological mechanisms and highlight an advantage over sham neurofeedback.…”
mentioning
confidence: 99%